PEMBERDAYAAN MASYARAKAT KELOMPOK DAGANG USAHA MIKRO KECIL DAN MENENGAH DI KELURAHAN SAGERAT WERU I KOTA BITUNG - RAMPENGAN, JESSICA; ROMPAS, WELSON; TAMPI, GUSTAAF (JURNAL ADMINISTRASI PUBLIK, 2019)
Micro, Small and Medium Enterprises are small scale economic activities of the people with business sectors which, in the majority are small business activities, the existence of this business in the midst of society has great and good benefits for the community for social welfare and reducing poverty but also as a driver of development benefits economy of the country. Community Empowerment is an effort to empower community communities through the realization of their potential manifestations. The goal to be achieved from community empowerment is to form individuals and communities to be independent, independence includes independence of thinking, acting, and controlling what is needed by a process. Through the learning process, the community will gradually acquire the ability or power from time to time. This study uses qualitative methods that are descriptive, namely to know or describe and explain the reality of the events studied or research on independent variables or one variable, that is without making comparisons or connecting with other variables. The results showed that the community of Umkm trading group in Sagerat Weru I Village in order to develop, the community and the government needed to actively work together to continue to provide guidance and entrepreneurship training and technical training to increase the skills of business people using small and medium micro business assistance. . In order for the Umkm merchant community, Sagerat Weru I Village to be able to empower all their businesses in terms of human resources, products, basic necessities and infrastructure to be reorganized so that buyers feel satisfied.Keywords: Community Empowerment,Trading Business.